The Relationship of the Learning Environment with the Activity of the Participants of Taklim Assembly Activities in Maransi Aia Pacah Padang - Kholimatus Sa'diah Aziz; Wirdatul Aini (Universitas Negeri Padang, 2023)
ABSTRACTThis research is motivated by the fact that the attendance of participants in the Nurul Haq Mosque Taklim activity in Maransi, Aia Pacah Village, Padang City 2021, is decreasing over time. This is presumably due to the less conducive learning environment. The purpose of this study is to see if there is a relevant relationship between the learning environment and the activeness of participants in the Nurul Haq Taklim Council activities in Maransi, Aia Pacah Village, Padang City 2021. This type of research is quantitative correlation. The population in this study were all 46 participants of the Taklim Mosque Nurul Haq Mosque in Maransi, Aia Pacah Village, Padang City 2021, with a sample size of 36 people. Swallowing data using a questionnaire or questionnaire. The data analysis technique uses the proportion formula and the Product Moment correlation formula. The results of the study 1) the learning environment of activities is not conducive; 2) Low participant learning activity; 3) There is a significant relationship between the learning environment and the active learning of participants. The statistical test obtained rcount = 0.826, it can be found a significant relationship between the learning environment of the participants in the Taklim Assembly activity in Maransi, Aia Pacah Village, Padang City.Keywords: Learning Environment, Activity, Taklim Assembly